Implementation of UMKM based on Participation Innovation And Digitalization In Achieving SDG’s Through Ced Prevention at PMB Sarfina Br Sembiring 2023 - Pasaribu, Riska Susanti; Manurung, Herna Rinayanti; Sinaga, Siti Nurmawan; Sinaga, Rosmani; Sinaga, Ribur; Surbakti, Imran Saputra; Marliani (LLDIKTI Wilayah 1, 2024)
In dealing with the complex problems of SEZs, lecturers and students of STIKes Mitra Husada Medan through grants from the Partnership-Based UMKM Development program produce PMT (Additional Food Packages) nutritious food Green Bean Cookies and Peanut Honey by utilizing the potential of local food and education pattern consumption. PMB Sarfina as place health services where the reach of this clinic business is expected to become wider with the implementation of innovation, digitalization and participation in the prevention of SEZ through technology in the service process health. Research methods This is study observational analytical with a cross sectional design. Participants are prospective brides, pregnant women and postpartum mothers who meet the inclusion and exclusion criteria. Retrieval and collection of research data was carried out using the probability purposive sampling method. A total of 82 participants took part in study This. This research was conducted at the PMB Sarfina Br Sembiring clinic in November-December 2023. Results & Conclusions are available influence participation, innovation, technology in reducing CED in prospective brides and grooms, pregnant women, and anticipating the problem of malnutrition in postpartum mothers. However, it has level insufficient knowledge in utilization Heath Store Partner Web Technology.